2019
DOI: 10.1371/journal.pone.0215873
|View full text |Cite
|
Sign up to set email alerts
|

“Primary care is primary care”: Use of Normalization Process Theory to explore the implementation of primary care services for transgender individuals in Ontario

Abstract: Background In Ontario, Canada, healthcare for transgender individuals is accessed through primary care; however, there are a limited number of practitioners providing transgender care, and patients are often on waiting lists and/or traveling great distances to receive care. Understanding how primary care is implemented and delivered to transgender individuals is key to improving access and eliminating healthcare barriers. The purpose of this study is to understand how the implementation of primary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Canadian-specific primary-care guidelines, from Ontario and British Columbia, are readily available online for practitioners to support the delivery of care to this vulnerable population (Dahl et al, 2015;Rainbow Health Ontario, 2015). In a recent study from Ontario, primary-care providers delivering transgender care identified the Ontario guidelines from Rainbow Health Ontario as their key resources in practice (Ziegler et al, 2019). Another example of online continuing education is the Trans Health Connection, which was funded by the Ontario Ministry of Health and Long-term care.…”
Section: Discussionmentioning
confidence: 99%
“…Canadian-specific primary-care guidelines, from Ontario and British Columbia, are readily available online for practitioners to support the delivery of care to this vulnerable population (Dahl et al, 2015;Rainbow Health Ontario, 2015). In a recent study from Ontario, primary-care providers delivering transgender care identified the Ontario guidelines from Rainbow Health Ontario as their key resources in practice (Ziegler et al, 2019). Another example of online continuing education is the Trans Health Connection, which was funded by the Ontario Ministry of Health and Long-term care.…”
Section: Discussionmentioning
confidence: 99%
“…33 For this study, the delivery of primary care services was explored, while an exploration of influences on implementation are reported elsewhere. 34 Using purposeful sampling, three cases were selected: a solo practice FFS, CHC, and FHT. A key informant from Rainbow Health Ontario (RHO) and the first author, identified eligible organizations known to provide primary care services to transgender individuals.…”
Section: Methodsmentioning
confidence: 99%
“…The Normalization Process Theory (NPT) [ 21 22 ] is a conceptual framework used in implementation science to examine how various complex healthcare interventions support clinical activities in different contexts [ 23 24 25 26 ]. We adopted the NPT in our analysis as it focuses on understanding “the processes through which a practice or practices become, (or do not become) routinely incorporated in everyday work of individuals and groups” ([ 22 ] p.2).…”
Section: Conceptual Frameworkmentioning
confidence: 99%